Uptake and emission of VOCs near ground level below a mixed forest at Borden, Ontario - Gordon, M.; Vlasenko, A.; Staebler, R. M.; Stroud, C.; Makar, P. A.; Liggio, J.; Li, S. -M.; Brown, S. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2014)
Understanding of the atmosphere/forest canopy exchange of volatile organic compounds (VOCs) requires insight into the deposition, emission, and chemical reactions of VOCs below the canopy. Between 18 July and 9 August 2009, VOCs were measured with proton-transfer-reaction mass spectrometry (PTR-MS) at six heights between 1 and 6 m beneath a 23 m high mixed-forest canopy. Measured VOCs included methanol, isoprene, acetone, methacrolein and methyl vinyl ketone (MACR + MVK), monoterpenes, and sesquiterpenes. There are pronounced differences in the behaviour of isoprene and its by-products and that of the terpenes. Non-terpene mixing ratios increase with height, suggesting predominantly downward fluxes. In contrast, the terpene mixing ratios decrease with height, suggesting upward fluxes. A 1-D canopy model was used to compare results to measurements with and without surface deposition of isoprene and MACR + MVK and emissions of monoterpenes and sesquiterpenes. Results suggest deposition velocities of 2.7 mm s(-1) for isoprene and 1.2 mm s(-1) for MACR + MVK and daytime surface emission rates of 63 mu g m(-2) h(-1) for monoterpenes. The modelled isoprene surface deposition is approximately 2% of the canopy-top isoprene emissions and the modelled emissions of monoterpenes comprise approximately 15 to 27% of the canopy-top monoterpene emissions to the atmosphere. These results suggest that surface monoterpene emissions are significant for forest canopy/atmosphere exchange for this mixed-forest location and surface uptake is relatively small for all the species measured in this study.